Factors related to perioperative nurses' job satisfaction and intention to leave. Issue 1 (3rd June 2019) - Lee, Seung Eun; MacPhee, Maura; Dahinten, V. Susan
Abstract: Aim: This study investigated factors associated with perioperative nurses' job satisfaction and their intention to leave. Recruitment and retention of nurses are particularly important in a specialist environment such as the perioperative setting where it is especially difficult to attract and retain nurses due to its unique environment. Methods: Cross‐sectional data were drawn from a larger study on nurses' work environments, conducted in one province of Canada. An e‐survey tool, consisting of validated scales, was administered by the provincial nurses' union to a stratified random sample of registered nurses. The study sample consisted of 113 perioperative nurses working in acute‐care hospitals. This study included two outcome variables (job satisfaction and intention to leave) and five predictor variables (three aspects of work environment, workload, and emotional exhaustion). Data were analyzed using multivariate linear and logistic regressions. Results: A multivariate linear regression model explained 49% (adjusted R 2 ) of variance in nurses' job satisfaction, and a multivariate logistic regression explained 19% (McFadden's R 2 ) of the variance in their intent to leave. After controlling for work status and other predictors, nurse‐physician relationship was significantly related to nurses' job satisfaction, and emotional exhaustion was the key predictor for both outcome variables. Conclusions: This study demonstrated that higher emotional exhaustion is associated with decreased job satisfaction and increased intention to leave among perioperative nurses. The findings suggest that nurse managers should create an empowering and open work environment that fosters perioperative nurses' job satisfaction and reduces their intention to leave.